Eﬀects of muscle energy techniques versus corrective exercise programme on pain, range of motion and function in patients with upper cross syndrome: a randomised clinical trial - Hanif, Arooj; Ahmad, Ashfaq; Ullah Arslan, Syed Asad; Asghar, Momna; Zaheer, Anna; Shaﬁq, Hira (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Upper crossed syndrome (UCS) is a common musculoskeletal issue that includes the dysfunctional tone of the muscles in the shoulder girdle or cervicothoracic region. The objective of the current study is to compare the eﬀects of muscle energy techniques with the National Academy of Sports Medicine-based exercise protocol on pain, range of motion, and dis-ability in patients with UCS.Methods. It was a single-blinded randomised clinical trial carried out in the Physiotherapy Department of the University of Lahore Teaching Hospital, Pakistan. Fifty patients with upper cross syndrome aged between 20 to 35 years were randomly allocated into two groups: group A (routine physical therapy combined with muscle energy techniques) and group B (routine physical therapy combined with the National Academy of Sports Medicine-based exercise protocol) for three sessions per week for total 8 weeks. Data were collected at baseline, 4th, 8th, and 12th week for assessing the long-term eﬀects of the treatment protocol as well. The Visual Analogue Scale, Neck Disability Index, and an inclinometer were used to measure the pain, disability, and range of motion of the cervical region, respectively. The data was analysed using SPSS version 23.0 (IBM, New York, USA).Results. Out of 50 participants, 30 were male and 20 were female. The mean age of all the participants in experimental group A was 29.76 ± 2.89 and that in experimental group B was 30.56 ± 2.48. At the 4th, 8th, and 12th week, pain and disability were signiﬁcantly (p-value < 0.05) reduced and cervical range of motion was signiﬁcantly (p-value < 0.05) improved within both groups. After 8 weeks of treatment, a signiﬁcant between-group diﬀerence was seen in favour of group A in terms of cervical range of motions (ﬂexion, extension, rotation, and side bending) with p-values of less than 0.05 and in favour of group B in terms of pain (p-value 0.03) and disability (p-value 0.04) was seen. These diﬀerences were maintained at the 12th week follow-up as well.Conclusions. This study concluded that both NASM (National Academy of Sports Medicine-based exercise protocol) and METs (muscle energy techniques) are eﬀective treatment options for people with upper cross syndrome. It was also concluded that METs are more eﬀective in improving Range of motion (ROM), while the NASM-based exercise protocol is more eﬀective in improving symptoms of pain and neck-related disability.
Keywords: muscle energy techniques; pain; range of motion; upper cross syndrome